Unique Pharmacological Properties of the Kappa Opioid Receptor Signaling Through G α z as Shown with Bioluminescence Resonance Energy Tranfer - Barnett, Miriam E; Knapp, Brian I; Bidlack, Jean M (Molecular pharmacology, 2020)
Opioid receptors (ORs) convert extracellular messages to signaling events by coupling to the heterotrimeric G proteins, G • Classic pharmacological methods, such as [ S]GTP S binding and inhibition of cyclic AMP production, allow for general opioid characterization, but they are subject to the varying endogenous G proteins in a given cell type. Bioluminescence resonance energy transfer (BRET) technology offers new insight by allowing the direct observation of G subunit-specific effects on opioid pharmacology. Using a Venus-tagged G and nanoluciferase-tagged truncated G protein receptor kinase 3, an increase in BRET signal correlated with OR activation mediated by a specific G protein. The magnitude of the BRET signal was normalized to the maximum response obtained with 10 µM 2-(3,4-dichlorophenyl)- -methyl- -[(1 ,2 )-2-pyrrolidin-1-ylcyclohexyl]acetamide (U50,488) for the kappa OR (KOR). Opioids reached equilibrium with the KOR, and concentration-response curves were generated. Although the full agonists U50,488, salvinorin A, nalfurafine, and dynorphin peptides were equally efficacious regardless of the G subunit present, the concentration-response curves were leftward shifted when the KOR was signaling through G z compared with other G i/o subunits. In contrast, the G subunit distinctly affected both the efficacy and potency of partial kappa agonists, such as the benzomorphans, and the classic mu opioid antagonists, naloxone, naltrexone, and nalmefene. For example, (-)pentazocine had EC values of 7.3 and 110 nM and maximal stimulation values of 79% and 35% when the KOR signaled through G z and G i1, respectively. Together, these observations suggest KOR pharmacology varies based on the specific G subunit coupled to the KOR. SIGNIFICANCE STATEMENT: Opioid receptors couple to various heterotrimeric Gαβγ proteins to convert extracellular cues to precise intracellular events. This paper focuses on how the various inhibitory Gα subunits influence the pharmacology of full and partial agonists at the kappa opioid receptor. Using a bioluminescent assay, the efficacy and potency of kappa opioids was determined. Opioid signaling was more potent through Gαz compared with other Gα proteins. These observations suggest that Gαz may impact opioid pharmacology and cellular physiology more than previously thought.